Sistem Komunikasi Augmentatif dan Alternatif Berbasis Tracking Realtime Mata - Yogi Ramadhani; Dita Dayu AW; Retno Supriyanti (Telematika, 2020)
Communication focuses on understanding of a person to another person, a simple communication can occur if there are similarities between the delivery of messages and people who receive messages. However, there are some people who lose communication skills or language and speech disorder which is a side effect of some diseases. One think to facilitate the problem is building a Augmentative and Alternative Communication (AAC) Systems. AAC is a communication method to support speaking or writing abilities for someone who have oral and writing disorders. In this research, eye-gaze boards used to implant AAC method. The computer programs created to implement that methods, with centroid iris tracking as input variable. The tests were carried out on various respondents with various eye shapes. The result of this research show that iris centroid could represent eyes direction, with six classifications (left – middle – right and upper – lower).